Normalised availability importance measures for complex systems. Issue 2 (17th February 2018) - Nouri Gharahasanlou, Ali; Ataei, Mohammad; Khalokakaie, Reza; Barabadi, Abbas
Abstract: Once the performance characteristics of a system have been determined, engineers are often faced with the task of identifying the critical components. The objective of this identification is to prioritise improvements in the systems and the efforts to bring these about in the areas that will have the most effect on the system's performance. Availability is an important metric, used to assess the performance of complex systems. Having the availability importance measure (AIM), which determines the importance of items regarding the availability of the system, can help designers and managers to improve performance and minimise the life cost of the system. This paper has developed an AIM for complex systems. Thereafter, the application of the developed importance measure is illustrated by a case study.